2019
DOI: 10.1093/jamia/ocz179
|View full text |Cite
|
Sign up to set email alerts
|

Improving the phenotype risk score as a scalable approach to identifying patients with Mendelian disease

Abstract: Objective The Phenotype Risk Score (PheRS) is a method to detect Mendelian disease patterns using phenotypes from the electronic health record (EHR). We compared the performance of different approaches mapping EHR phenotypes to Mendelian disease features. Materials and Methods PheRS utilizes Mendelian diseases descriptions annotated with Human Phenotype Ontology (HPO) terms. In previous work, we presented a map linking phecod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…Enabling large scale integration of biomedical knowledge with clinical patient data requires robust and accurate mappings between standardized clinical terminology concepts and ontologies, like the HPO. Existing work has demonstrated the power of the HPO to enrich clinical data including craniofacial and oral phenotypes ( 57 ), rare and Mendelian disease ( 58 , 59 ), and infectious disease ( 60 ). There have also been more generalized mapping efforts aimed at aligning different clinical terminologies to the HPO including free-text narratives ( 61 ) and structured data like diagnosis codes ( 62 , 63 ).…”
Section: Ehr Integrationmentioning
confidence: 99%
“…Enabling large scale integration of biomedical knowledge with clinical patient data requires robust and accurate mappings between standardized clinical terminology concepts and ontologies, like the HPO. Existing work has demonstrated the power of the HPO to enrich clinical data including craniofacial and oral phenotypes ( 57 ), rare and Mendelian disease ( 58 , 59 ), and infectious disease ( 60 ). There have also been more generalized mapping efforts aimed at aligning different clinical terminologies to the HPO including free-text narratives ( 61 ) and structured data like diagnosis codes ( 62 , 63 ).…”
Section: Ehr Integrationmentioning
confidence: 99%
“…Rapid and accurate variant interpretation remains a challenge in clinical genetics. We have previously showed that PheRS could augment variant interpretation 9,10 . Using PheRS including new phenotypes identified from the PheWAS serves as a test of the potential utility of these new phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, our ability to predict the pathogenicity of rare genetic variants remains poor, and these actionable genes still contain many variants of uncertain significance (VUS). We have previously demonstrated that aggregating related EHR phenotypes for Mendelian diseases could aid in variant interpretation 9,10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other risk score models based only on clinical symptoms, or integrating these with laboratory data have recently been proposed 14,15 . As we did not have access to these models, including the script, model parameters, HPO terms, laboratory variables and ICD-codes, we were unable to replicate and to test them on the family study of the HEIRS cohort.…”
Section: Discussionmentioning
confidence: 99%